Carpenter syndrome in a patient from Tanzania. Issue 3 (24th December 2020) - Lodhia, Jay; Rego‐Garcia, Iago; Koipapi, Sengua; Sadiq, Adnan; Msuya, David; Spaendonk, ResieVervenne‐van; Hamel, Ben; Dekker, Marieke
Abstract: Carpenter syndrome (acrocephalopolysyndactyly type II) is a rare autosomal recessive disorder. It was clinically diagnosed in a female baby with polysyndactyly and craniosynostosis in a referral clinic in Northern Tanzania. In the RAB23 gene, a previously described homozygous variant c.82C>T p.(Arg28*) was detected that results in a premature stop codon. Both parents were demonstrated to be heterozygous carriers of this variant. Herewith, its pathogenicity is proved. A literature search suggests this is the first molecularly confirmed case of Carpenter syndrome in continental Africa.